Electrical properties dependence on substrate temperature of sputtered ZnO nanoparticles thin films on teflon substrates - Nur Sa’adah, Muhamad Sauki; Herman, Sukreen Hana; Ani, Mohd Hanafi; Mohamad Rusop , Mahmood (Trans Tech Publications, Switzerland, 2013)

(untitled)
Zinc oxide (ZnO) thin films were deposited on teflon substrates by RF magnetron sputtering at different substrate temperature. The effect of substrate temperature on ZnO thin films electrical and structural properties were examined using current-voltage (I-V) measurement, and xray diffraction (XRD) It was found that the electrical conductivity and resistivity of the ZnO thin film deposited at 40oC was the highest and lowest intensity accordingly. This was supported by the crystalline quality of the films from the x-ray diffraction (XRD) results. The XRD pattern showed that the ZnO thin film deposited at 40oC has the highest intensity with the narrowest full-width-athalf- maximum indicating that the film has the highest quality compared to other thin film.